Assessment of Physical Literacy Levels of Elementary School Students in Physical Education Learning Using CAPL-2: A Cross-Sectional Study - Johan Irmansyah; Mujriah; Elya Wibawa Syarifoeddin; Herman Syah (Слобожанський науково-спортивний вісник)
Background and Study Aim. This study aims to analyze and classify the physical literacy levels of elementary school students using CAPL-2 and identify potential differences based on gender across three key domains: Physical Competence, Motivation & Confidence, and Knowledge & Understanding.